Pancreatic Cancer Prediction Through an Artificial Neural Network - Muhammad, Wazir; Hart, Gregory R.; Nartowt, Bradley; Farrell, James J.; Johung, Kimberly; Liang, Ying; Deng, Jun (Frontiers in Artificial Intelligence, 2019)
Early detection of pancreatic cancer is challenging because cancer-specific symptoms occur only at an advanced stage, and a reliable screening tool to identify high-risk patients is lacking. To address this challenge, an artificial neural network (ANN) was developed, trained, and tested using the health data of 800,114 respondents captured in the NHIS and PLCO datasets, including 898 patients diagnosed with pancreatic cancer. Prediction of pancreatic cancer risk was assessed at an individual level by incorporating 18 parameters into the neural network. The established ANN model achieved a sensitivity of 87.3% and 80.7%, a specificity of 80.8% and 80.7%, and an area under the receiver operating characteristic curve of 0.86 and 0.85 for the training and testing cohorts, respectively. These results indicate that our ANN can be used to predict pancreatic cancer risk with high discriminatory power, and may provide a novel approach to identify patients at higher risk for pancreatic cancer who may benefit from more tailored screening and intervention.